E. J. Josey : transformational leader of the modern library profession - Chancellor, Renate L. (Lanham, Maryland : Rowman & Littlefield, 2020)
'This book examines the life and career of librarian, educator and activist E.J Josey. During Josey's professional life, which spanned fifty-five years, he worked as a librarian (1953-1966), an administrator of library services (1966-1986), and as a professor of library science (1986-1995)'--
Journey towards leadership-- A dreamer with a tiny spark-- Early career : the transformation begins -- A leader rises up -- A model for leadership in LIS -- Legacy of a transformative leader.
Includes bibliographical references and index.
Keywords: Josey, E. J., -- 1924-2009.; American Library Association -- History; Librarians -- United States -- Biography; African American librarians -- Biography; African Americans and libraries; Minorities in library science -- United States -- History -- 20th century